A Revisit to the Pretargeting Concept—A Target Conversion - Liu, Guozheng (Frontiers in Pharmacology, 2018)
Pretargeting is often used as a tumor targeting strategy that provides much higher tumor to non-tumor ratios than direct-targeting using radiolabeled antibody. Due to the multiple injections, pretargeting is investigated less than direct targeting, but the high T/NT ratios have rendered it more useful for therapy. While the progress in using this strategy for tumor therapy has been regularly reviewed in the literature, this review focuses on the nature and quantitative understanding of the pretargeting concept. By doing so, it is the goal of this review to accelerate pretargeting development and translation to the clinic and to prepare the researchers who are not familiar with the pretargeting concept but are interested in applying it. The quantitative understanding is presented in a way understandable to the average researchers in the areas of drug development and clinical translation who have the basic concept of calculus and general chemistry.